A class of double integrals involving Gauss's hypergeometric function - S., Jun; Kilicman, Adem; I., Kim; K., Rathie (Universiti Putra Malaysia, 2020)
One hundred interesting double integrals involving Gauss's hypergeometric function in the form of four general integrals (twenty five each) have been evaluated in terms of gamma function. More than two hundred special cases have also been given.